Difference of reynolds crisis aspects on soccer balls and their panels - Sakamoto, Y.; Ito, S.; Hiratsuka, M. (Proceedings, 2020)
The soccer ball panel pattern, which changes every World Cup, greatly affects the ball`s aerodynamics and flight characteristics. In this study, the fluid force of 11 soccer balls with different panel patterns was measured by wind tunnel tests. The drag crises with different Reynolds numbers were confirmed depending on the panel shape. To understand this, the shapes of panel grooves were measured and the relationship between them was investigated. The flow separation point was also visualized by the oil film method and the particle image velocimetry (PIV) analysis. The separation points were confirmed to be different depending on the panel groove by the oil film method in a supercritical Reynolds region. The flow separation points were found to be almost the same position in the subcritical and supercritical state and to be partly different around the Reynolds number of drag crisis.